Electronic Signature in Provening the Criminal Act of Forgiveness - Maman Budiman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The electronic signature abuser has violated the criminal law. The crime can be categorized as a criminal act of forgery as regulated in the Criminal Code Article 263 paragraph 1. To be subject to sanctions in Article 263 paragraph (1) of the Criminal Code, the forged letter must be a letter that can issue rights such as certificates, can issue an agreement such as an agreement. debt, can issue a debt such as a receipt and a letter that may be used as a statement for an act or event such as a birth certificate. The current development of authentic documents such as birth certificates, diplomas, sale and purchase certificates, payment receipts using electronic signatures, where the electronic signature may not be recognized by the original signature holder. From the background of the problem that will be studied by the author is whether electronic signatures are legal evidence in accordance with Article 184 paragraph 1 of the Criminal Procedure Code, and how to prove the authenticity of electronic signatures in criminal cases of forgery. The research method used in this paper is to use an interdisciplinary method that combines several legal sciences, such as criminal law, criminal procedural science and evidentiary law. The conclusion in this paper is that electronic signature evidence can be categorized as evidence as regulated in Article 184 paragraph 1 of Law Number 8 of 1981 concerning the Criminal Procedure Code because the results of a letter issued by the Criminal Laboratory of the Police Headquarters can be categorized as letter evidence because it is issued by an authorized institution. Proof of the authenticity of electronic signatures in criminal cases of forgery must be tested first at the Criminal Laboratory (Labkrim) of the National Police Headquarters (Mabes), whether the signature is authentic or not, after that it is matched with the original signature. After doing further research to see whether the signature is used as a signature.